Are Radiographs Necessary Before Kirschner Wire Removal in Supracondylar Fracture of Humerus in Children Who Have Undergone Operative Procedure? - Junaid Khan, Riaz Ahmed, KanzaBatool, Mariam Niaz, KiranSiddiqui, HashimRiaz (Journal of Rawalpindi Medical College, 2016)
Background: To assess the need for radiograph one day prior to Kirschner wires removal in supracondylar humerus fracture patients, who had undergone percutaneous wire fixation. Methods: In this prospective cohort study 100 patients with supracondylar humerus fracture were included. Patients were divided into two groups. Group A was the one in which the radiographs (AP and lateral view) were obtained one day prior to kwire removal, whereas no prior x-rays were obtained before k-wire removal in group B. All patients were operated by percutaneous k-wiring, position and angles of k-wires confirmed under fluoroscope. The operated limb was immobilized in a back slab after k-wire fixation. Postoperative radiographs (AP and lateral view) obtained for all patients before being discharged. First follow-up was after 2 weeks of surgery for Stitch removal. Second follow-up,3 weeks after surgery to remove the back slab. Third follow up at almost 4 weeks of surgery for k-wire removal. Baumann’s angle was calculated and compared from radiographic evaluation that was done during surgery and the final follow up X-ray. Results. Out of the 100 patients, 57 were male while 33 were females. Supracondylar humerus fractures were classified into flexion and extension type. Patients in group A (n=50) had a mean age 5.381.308 whereas in group B (n=50) it was 5.241.271. In group A, the mean number of post-operative days prior to k-wire removal was 27.162.881 while for group B it was 27.303.046 (p-value 0.814). Patients in group A had a mean difference in Baumann’s angle of 2.3240.041 while in group B 2.3290.023 (p-value 0.452). K-wires were not retained in any of the patients who underwent radiography one day before the expected day of their removal Conclusion: X-rays are not a requisite before Kirschner wire removal in supracondylar fracture of humerus in children. This not only saves the child and the family from anxiety but also prevents unnecessary radiation exposure, which may harm the child in long run.